2022
DOI: 10.3390/cancers14215192
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Depression and Anxiety in Adults with High-Grade Glioma: A Literature Review and Findings in a Group of Patients before Chemoradiotherapy and One Year Later

Abstract: High-grade glioma (HGG) is associated with several external and internal stressors that may induce mood alterations at all stages of the disease. Symptoms of depression and anxiety in persons with glioma have multifactorial etiology and require active follow-up. We reviewed the literature data on the prevalence, mechanisms likely involved in the etiology of mood alterations in persons with HGG and psychosocial interventions found beneficial in treating these symptoms. We also investigated the prevalence and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“… 11 Regarding glioma, previous studies reported memory and executive deficits in patients with frontal glioma, 34 , 35 impaired empathy ability in those with insular glioma, 36 verbal working memory deficits in those with low‐grade glioma, 37 and anxiety and depression in those with high‐grade glioma. 38 Although each subtype has unique feature, our study mainly focuses on delineating the neuropsychological distinctions between PitNET and glioma patients. The aim is to facilitate the initial screening and assessment of neuropsychological status rather than individualized assessment.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Regarding glioma, previous studies reported memory and executive deficits in patients with frontal glioma, 34 , 35 impaired empathy ability in those with insular glioma, 36 verbal working memory deficits in those with low‐grade glioma, 37 and anxiety and depression in those with high‐grade glioma. 38 Although each subtype has unique feature, our study mainly focuses on delineating the neuropsychological distinctions between PitNET and glioma patients. The aim is to facilitate the initial screening and assessment of neuropsychological status rather than individualized assessment.…”
Section: Discussionmentioning
confidence: 99%